Using flat concurrent Prolog in system modeling - Dotan, Y.; Arazi, B. (IEEE transactions on software engineering, 1991)
The flat concurrent Prolog (FCP) language, which enables the implementation of synchronization through data flow, communication through shared variables, parallelism through the reduction of the AND components in the clause's body, and indeterminacy through guarded commands, is discussed. It is shown that FCP, used in conjunction with Petri net methods, forms a powerful tool in the modeling of parallel systems that involve concurrency. The simulation of systems represented by various types of Petri nets is achieved using the reduction process of FCP. AND parallelism supports free competition among conflicting enabled transitions. A structural analysis of systems is provided using the metaprogramming technique.< >